Democratizing Public Management Towards Practice-Based Theory - Struminska-Kutra, Marta (Springer International Publishing, 2018)
This book argues that contemporary society in general, and public administration specifically, can benefit from more reflexive learning processes through democracy and public involvement. It identifies the most central social practices, dilemmas, and challenges for public management as well as the mechanisms needed to enact institutional change. Offering a model of reflexivity and learning in the face of public dispute, it explores phenomena such as problem solving, democratization, public learning, and uncertainty to address certain tensions in governance theory and practice. Through a range of well-sourced case studies, this book demonstrates how institutions can manage difficult situations by not only resolving the conflict but addressing the underlying problem. It uses both theoretical and practical approaches to observe the micro foundations of political behavior and its institutional underpinnings, and will be a valuable resource for public administration researchers, practitioners, and graduate students seeking empirical studies of learning processes in the public sphere. .